QARAQALPAQ XALÍQ DÁSTANÍ «SHÁRYAR»: JIYNALÍWÍ, BASÍP SHÍǴARÍLÍWÍ HÁM IZERTLENIWINIŃ AYÍRÍM MÁSELELERI - Keńesbaeva, Sh.K. (SCIENCE and SOCIETY, 2019)
The article deals with the genre peculiarities of the Karakalpak folklore epos «Shariyar», the other peoples don't have the analogy to it. The author of the article compares different points of view on this issue in Karakalpak folklore and comes to the concuision that this epos is neither social-realistic, nor a work with an external plot, but it is a mythologic-fairy tale epos.